1999
DOI: 10.1149/1.1392575
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐Determining Step Investigations of Oxidation Processes at the Positive Plate during Pulse Charge of Valve‐Regulated Lead‐Acid Batteries

Abstract: In order to develop electric vehicles (EVs), electrochemical scientists and engineers have paid great attention to the study of batteries in recent years. Now, while new types of batteries are still in development, the valve-regulated lead-acid (VRLA) battery is a near-term candidate for EV applications in mass markets. 1 A key usage issue is the possibility of fast recharge. More recently, much work has been carried out on pulse charging of lead-acid batteries. 2-7 The recharge time for valve-regulated lead-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The first mathematical models appeared at the beginning of the 1970s when computers enabled the development of this kind of application. These models, [1][2][3][4][5][6][7][8][9][10][11] detailed in Table I, were progressively applied to the lead-acid electrodes and cells of flooded batteries. Since the 1990s, they have been applied to sealed batteries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first mathematical models appeared at the beginning of the 1970s when computers enabled the development of this kind of application. These models, [1][2][3][4][5][6][7][8][9][10][11] detailed in Table I, were progressively applied to the lead-acid electrodes and cells of flooded batteries. Since the 1990s, they have been applied to sealed batteries.…”
mentioning
confidence: 99%
“…11 The results obtained at a high current density ͑Ͼ100 mA/cm 2 ͒ and a normal acid concentration ͑5 M͒ demonstrate that the available capacity of the negative electrode is limited by a thickness of insulating PbSO 4 like in the positive one. More recently, the positive electrode gassing of sealed battery, under pulse current in charge, was studied by Guo et al 6 The proposed model showed that the electrode polarization, oxygen evolution, and loss of water can be inhibited by using a pulse discharge and/or by prolonging the off time of the pulse charge.…”
mentioning
confidence: 99%
“…It should be noted that there are reports in the literature of considerable higher exchange current densities for the reaction. For example, LaFollette and Bennion 28 use a value of 1.78 mA/cm 2 , while Guo et al 29 and Carr and Hampson 30 use 0.32 mA/cm 2 , all three authors suggesting that the electrode reaction is facile. The latter value appears to have originated from a paper by Aguf, 31 where the exchange current density of this reaction was measured using impedance spectroscopy.…”
Section: ͓20͔mentioning
confidence: 99%
“…The pulsedcurrent charge not only shortens the charge time but also overcomes PCL 2 and hence prolongs the cycle life of the batteries. [9][10][11][12] In an optimized design, the ratio of the active mass between the positive and negative plates is important to the battery life. 13,14 As the utilization of PAM is much lower than that of the negative active mass, great attention has been paid to the investigations on PAM utilization in the past decades.…”
mentioning
confidence: 99%